ANSI C63.2-2016 (Revision of ANSI C63.2-2009) - Redline : American national standard for specifications of electromagnetic interference and field strength measuring instrumentation in the frequency range 9 kHz to 40 GHz (IEEE, 2017)
Requirements for measuring instruments used for electromagnetic interference (EMI) measurements are provided, involving quasi-peak, peak, and average detection in the frequency range 9 kHz to 40 GHz.